Punch Incision with Secondary Healing (PISH) Technique for Benign Facial Lesions: An Institutional Experience in 307 Patients - Yadav, Sudeep Pradeep; Gharwade, Chandrakant Rambhau; Khatri, Gayatri Nagindas (Indian Journal of Plastic Surgery, 2021)
Background Multiple or solitary facial lesions pose a unique challenge to the attending surgeon in terms of delivering the best cosmetic outcome. There are various methods in dealing with them and the preference of using them is based on the surgeon’s experience, patient expectations, and availability of instruments. One such tool, skin-punch, primarily designed for a biopsy can play a very important therapeutic role in this era of keyhole surgery. In this paper, we assess the technique of punch incision with its combination of secondary healing for various facial lesion.Methods This observational study, a total of 307 patients with solitary or multiple benign facial lesions were treated with punch incision technique using 2 to 6 mm sterile, disposable skin biopsy punches. Subsequently, the wounds were managed with healing with secondary intention.Results In our series all superficial wounds epithelized by 7 to 14 days while the deeper lesions epithelized by 14 to 28 days. We had three recurrences which were managed by fusiform excision and one patient had surgical site infection which was managed conservatively. On application of our self-devised facial scar scoring system (SCAR or Scar Cosmesis Assessment and Rating)3 on all the scars, the mean score was 6 at 1 year followup.Conclusion Punch incision with healing by secondary intention is a relatively easy, effective, single-stage office procedure. This method can be considered as an alternative method for the removal of various skin lesions, especially on face, thus providing a simple solution to complex problems.
Keywords: punch incision; healing by secondary intention; facial lesions; skin biopsy punch; PISH; SCAR